Comparison of explicit values clarification method (VCM), implicit VCM and no VCM decision aids for men considering prostate cancer screening - Baptista, S (2020)
H4A Primary Healthcare Research Network scholars programme for support of research in the protocol design phase. This article will also be supported by National Funds through FCT - Fundação para a Ciência e a Tecnologia,I.P., within CINTESIS, R&D Unit (reference UIDB/4255/2020).